Influence of control parameters on the crack paths in the aluminum alloy 2024 under bending - E. Marcisz; D. Rozumek; Z. Marciniak (Fracture and Structural Integrity)
The paper presents development of crack paths in aluminium alloy 2024. Fatigue tests were carried out for specimens with rectangular cross-section. The specimens were put to bending at controlled energy parameter amplitude and bending moment amplitude. The proposed method of conducting research with the controlled energy parameter has been presented in [1]. The energy parameter model proposed by Macha has been used in the tests. Tests with controlled energy parameter amplitude allow observing crack growth depending on maximum shearing stress surface. Tests with controlled bending moment amplitude allowed observing two types of crack paths